2000
DOI: 10.1034/j.1399-0012.2000.140403.x
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous pancreas‐kidney transplantation: portal versus systemic venous drainage of the pancreas allografts

Abstract: Simultaneous pancreas-kidney (SPK) transplantation is considered a valid therapeutic option for patient with type I diabetes mellitus and end-stage diabetic nephropathy. This study was performed to determine whether the technique of pancreas venous drainage affects patient survival as well as graft survival and function. From October 1996 to April 1999 34 uremic patients with type I diabetes mellitus were randomly assigned to two groups: the first group (SV group = 17) received SPK transplantation with systemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 17 publications
1
38
0
Order By: Relevance
“…However, neither large registry analyses nor prospective cohort studies have been able to corroborate these purported benefits (Table 9) [1,33,[39][40][41][42][44][45][46][49][50][51][52][53][112][113][114][115][116][117][118][119][120][121][122][123] . Conversely, when comparing the three major techniques of pancreas transplantation, there are likewise no well controlled studies to suggest any major drawbacks of portal-enteric vs either systemic-bladder or systemic-enteric drainage.…”
Section: El-hennawy H Et Al Exocrine Drainage In Pancreas Transplantsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, neither large registry analyses nor prospective cohort studies have been able to corroborate these purported benefits (Table 9) [1,33,[39][40][41][42][44][45][46][49][50][51][52][53][112][113][114][115][116][117][118][119][120][121][122][123] . Conversely, when comparing the three major techniques of pancreas transplantation, there are likewise no well controlled studies to suggest any major drawbacks of portal-enteric vs either systemic-bladder or systemic-enteric drainage.…”
Section: El-hennawy H Et Al Exocrine Drainage In Pancreas Transplantsmentioning
confidence: 99%
“…The incidence of surgical complications is also similar by type of transplant (SPK compared to solitary pancreas transplantation) [1][2][3] . Leaks from the allograft duodenum have been reported to occur in 5%-20% of bladder-drained and 5%-8% of bowel-drained pancreas transplants [9,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][67][68][69][70][71][72][73]80,[91][92][93][94][95] . Increasing experience with enteric exocrine drainage is likewise associated with a decreased rate of technical complications [9,38,80,[96][97][98][99][100][101][102][103] .…”
Section: El-hennawy H Et Al Exocrine Drainage In Pancreas Transplantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Being familiar with multiple surgical techniques of PT is helpful because the optimal technique may need to be individualized based on anatomic issues. Purported benefits of PT with portal venous outflow include technical, metabolic, and immunologic "advantages" [2][3][4][5][6][7][8][9]12]. However, these benefits have not been confirmed by either prospective cohort studies, randomized controlled trials, or large analyses based on registry databases [1,[4][5][6][7][8]12].…”
Section: Discussionmentioning
confidence: 99%
“…However, the potential of portal-enteric drainage has never been fully realized as it currently accounts for only 18% of SKPT and PAK and 10% of PTA transplants [1]. A number of studies have demonstrated no major or consistent differences in outcomes for bladder-drained or enteric-drained PTs with either portal or systemic venous drainage [4][5][6][7][8]. Although nearly all PTs are currently performed with one of the three above techniques, current philosophy dictates that the most appropriate technique to be performed is the one with which the surgical team has the most experience.…”
Section: Introductionmentioning
confidence: 99%